2017
DOI: 10.1186/s12302-016-0099-0
|View full text |Cite|
|
Sign up to set email alerts
|

Possible health impacts of Bt toxins and residues from spraying with complementary herbicides in genetically engineered soybeans and risk assessment as performed by the European Food Safety Authority EFSA

Abstract: BackgroundMON89788 was the first genetically engineered soybean worldwide to express a Bt toxin. Under the brand name Intacta, Monsanto subsequently engineered a stacked trait soybean using MON89788 and MON87701—this stacked soybean expresses an insecticidal toxin and is, in addition, tolerant to glyphosate. After undergoing risk assessment by the European Food Safety Authority (EFSA), the stacked event was authorised for import into the EU in June 2012, including for use in food and feed. This review discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Such actions would imply a change in emission of suites of chemicals, with those suites including the set of chemicals of high priority within the land use. Abating chemical risks can utilize a suite of options, not solely a chemo‐centric approach (National Research Council 2009; Munthe et al 2017); and it was, for example, shown earlier that an analysis of spatial associations between emission points and water bodies with sensitive functions (drinking water production, protected nature) can be a basis to reduce impacts via smart spatial arrangements (Coppens et al 2015) and that clever strategies may be utilized to reduce adverse effects of chemicals and other water quality parameters (Malaj et al 2014; Barclay et al 2016). From upstream to downstream, land‐use influences on smaller tributaries may be characterized by mixtures with greater exposures and simpler composition, with a “land‐use dilution” effect in the downstream direction (López‐Serna et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such actions would imply a change in emission of suites of chemicals, with those suites including the set of chemicals of high priority within the land use. Abating chemical risks can utilize a suite of options, not solely a chemo‐centric approach (National Research Council 2009; Munthe et al 2017); and it was, for example, shown earlier that an analysis of spatial associations between emission points and water bodies with sensitive functions (drinking water production, protected nature) can be a basis to reduce impacts via smart spatial arrangements (Coppens et al 2015) and that clever strategies may be utilized to reduce adverse effects of chemicals and other water quality parameters (Malaj et al 2014; Barclay et al 2016). From upstream to downstream, land‐use influences on smaller tributaries may be characterized by mixtures with greater exposures and simpler composition, with a “land‐use dilution” effect in the downstream direction (López‐Serna et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are some further relevant issues in the risk assessments of HT GE plants and pesticides that require the establishment of a step-by-step interface process during the approval procedure [94]: for example, it should be taken into account that there may be specific interactions between residues of herbicides and plant constituents. This is particularly relevant for natural allergens and phytoestrogens in plants, since there are several indications that their risks to health can increase by interactions with compounds derived from glyphosate-based herbicides.…”
Section: Some Further Overlapping Issuesmentioning
confidence: 99%
“…Upon publication of the original article [ 1 ], the authors noticed that the number of the event mentioned in the first sentence of the article was incorrect. Instead of: MON89788, the correct number is: MON87701 and therefore the first sentence of the article should read:…”
Section: Erratum To: Environ Sci Eur (2017) 29:1 Doi 101186/s12302-0mentioning
confidence: 99%